ESTIMATION OF LAND SURFACE TEMPERATURE IN BUNGO DISTRICT USING THERMAL CHANNELS OF LANDSAT 8 IMAGES - Annisa Firstyandina; Febriandi Febriandi (International Remote Sensing Applied Journal, 2020)
The purpose of this study was to determine the land surface temperature in Bungo Regency using the Landsat 8 image thermal channel by carrying out three stages: (1) Mapping the comparison of vegetation density in 2016 and 2021 using the NDVI (Normalized Difference Vegetation Index) method. (2) Mapping land surface temperatures in 2016 and 2021 using the Land Surface Temperature method. (3) Knowing the relationship between LST and NDVI using the Correlation Person test. The results of the study explain the comparison of vegetation density using the Normalized Difference Vegetation Index (NDVI) method in 2016 and 2021 in Bungo Regency. In 2016 the classification is very dense with an area of ​​124,871 Ha, the classification dense with an area of ​​115,732 Ha, the classification medium with an area of ​​98,536 Ha, the classification is rare with an area of ​​71,920 Ha, and very rare classification with an area of ​​54,839 Ha. Whereas in 2021 the very dense classification will decrease to 117,216 Ha, the dense classification will decrease to 112,365 Ha, the moderate classification will decrease to 95,892 Ha, the rare classification will increase to 79,310 Ha, and the very rare classification will increase to 61,084.